Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1002/(sici)1521-4079(199911)34:9<1191::aid-crat1191>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Optical Characterization of Oxygen doped CuInSe2 Crystals

Abstract: From a combined study of the electrical properties between room temperature and 77 K and optical absorption at 300 K of bulk CuInSe 2 samples doped with different oxygen concentrations, two shallow acceptor levels are found. The activation energy E A1 and E A2 of these levels in the dilute limit tends to be around 30 and 36 meV, respectively. The increase of E A1 and decrease of E A2 with the increase of oxygen content can be explained consistently on the basis that the ratio of Cu to In atoms increases with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Such a level has 31 meV as the ionization energy. This is probably due to an acceptor state since the samples changed conductivity from n to p-type after implantation, which agrees well with published data on doping CuInSe 2 with Oxygen where an acceptor state with an ionization of 30 meV has been reported [8]. The defect level appearing as a peak at hν = 0.96 eV, denoted as L 1 , remained unchanged even after the implantation at both doses.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Such a level has 31 meV as the ionization energy. This is probably due to an acceptor state since the samples changed conductivity from n to p-type after implantation, which agrees well with published data on doping CuInSe 2 with Oxygen where an acceptor state with an ionization of 30 meV has been reported [8]. The defect level appearing as a peak at hν = 0.96 eV, denoted as L 1 , remained unchanged even after the implantation at both doses.…”
Section: Resultssupporting
confidence: 91%
“…On the other hand, there is some experimental evidence that the incorporation of oxygen into CuInSe 2 affects considerably the acceptor concentration and may give rise to an additional new acceptor state . In addition, it has been found that the incorporation of In 2 O 3 in CuInSe 2 thin films leads to an increase in the ratio of copper to indium atoms .…”
Section: Introductionmentioning
confidence: 99%